PENGARUH REALISASI ANGGARAN BELANJA MODAL TERHADAP TOTAL BELANJA CV SINAR FAJAR PRIMA BANDUNG - HASBI BASITH SUKARNO; Wulan Meidawati (POLITEKNIK PIKSI GANESHA, 2022)
The research was aimed to know the influence of capital budget realization to total expending at CV Sinar Fajar Prima Bandung. The research method used quantitative method throught descriptive approarch. The data collection used observation, and study literate. The data analysis used perason product moment, linear regration, and coefficient of determination.. The result indicates that there is a statistical correlation between capital budgeting and total expenditure. This is shown by the statistical coefficient test of 99,8, which also proves that there is a strong and positive correlation between the variables. Based on the finding of this research, the regression model is as follow: Y = -4304009+ 0.994x, which means every increase of capital budget will be followed by an increase in total expenditures of 0.994% added by a constants of - -4304009. The findings also resulted in a coefficient of determination of 99.8%, this means that the capital budgeting affects 99.8% of the changes in the total expenditure, while the other 0.2% is affected by other variables. The suggestions given to improve problems are; 1) data input should be conducted carefully; 2) there should be the addition of capital budget; 3) Prepared facility and place for file or documents storage so can be easy to search later. Keywords: Capital budget realization, total expenditure.